Development and Validation of Montelukast with Grape/Licorice Juices and its Application to Pharmacokinetic Studies by LC/MS - Hamad, Mohammed; Raad, Rafif; Mallah, Eyad; Zakaria , Zainab; Arafat , Tawfiq; Abu Dayyih, Wael (Indonesian Journal of Pharmacy, 2020)
A simple, rapid and sensitive simultaneous method for validation and determination of Montelukast in rat plasma in the presence of grape and licorice juices has been done by using High Performance Liquid Chromatography–Mass Spectrometry (HPLC/MS). A mixture of (77.5 % methanol, 22.5 % of 0.2% FA in water) was used as a mobile phase, ACE 5 C8 column (50 X 2.1 mm, 5μ), and a flow rate of 0.1 ml/min were used, the auto-sampler injection volume was 5 microliters, and candesartan was used as an internal standard. According to the result obtained, the precision of predicted measurements for Montelukast was good (mean CV % 0.05) of grape on Montelukast Cmax (163.492 ng/ml ±113.27). Neither licorice gives significant decrease in the Montelukast Cmax (143.861ng/ml ±54.52), its only delay the average Montelukast Cmax to half an hour. Even for the AUC, there were no significant difference between Montelukast alone and Montelukast with grape, and Montelukast with licorice (P>0.05). The kinetic data shows that Montelukast plasma level was the same with both combination of Montelukast and grape, and Montelukast and licorice.